Panic, Psycho-Behavioral Responses, and Risk Perception in the Earliest Stage of the COVID-19 Pandemic in China - Zhang, Weiyu; Zou, Changqing; Sznajder, Kristin K.; Cui, Can; Fu, Jiahui; He, Shan; Peng, Qinqi; Chen, Qiongli; Yang, Xiaoshi (Frontiers in Medicine, 2022)
Background: The Coronavirus Disease-19 (COVID-19), a rising global pandemic, has triggered psychological crises among the public. Panic, a severe symptom of mental disorders, is increasing in the public in China and it is urgent to provide research for intervention development. Objectives: This study aimed to assess the prevalence of public panic in China during the earliest stage of the COVID-19 pandemic, and to explore the associated psychological behavioral responses and public's risk perception of the pandemic. Methods: A cross-sectional study using a web-based survey with convenience sampling was conducted with 2,484 participants nationally from February 11 to February 24, 2020 in China. A self-developed questionnaire was applied to assess the prevalence of public panic and its associated factors. Multivariable logistic regression analysis was applied to assess the risk and protective factors of public panic. Results: There were 23.39% (581/2,484) of the participates reported experiencing panic during the earliest stage of the COVID-19 pandemic. Taking temperature repeatedly, being nervous in a crowd, being suspicious of infection in the family, being worried about the future; and worries about high infectivity of the COVID-19, lack of effective therapies, and wide impact of the COVID-19 pandemic increased the odds of public panic. Whereas, avoiding gatherings during holidays were negatively associated with the odds of public panic. Conclusions: Psycho-behavioral responses were closely associated with public panic during the earliest stage of the COVID-19 pandemic in China. Defusing excessive health-related worries, guidance of appropriate self-protective behaviors, strengthening of health education in communities, and available treatment for mental disorders should be adopted to monitor the psychological responses and to guide the behaviors of the public.